ANALISIS PERMASALAHAN ANAK AUTIS DI SEKOLAH INKLUSI SMK NEGERI 9 KOTA PADANG - Nurul Aina Koto; Suryadi Suryadi; Triyono Triyono (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2023)
This study aims to find out and explain the social abilities of autistic children, as well as to find out the efforts of teachers to overcome the difficulties of socializing autistic children at SMKN 9 Padang a school that has an inclusion class. This type of research uses qualitative methods with a case study approach. The research subjects were class IX students with autistic disorders. Data was collected using the method of observation, interviews, and documentation. Then to test the validity of the data using a credibility test. The credibility test was carried out using a triangulation technique. The results of interviews with counseling guidance teachers and with students who discussed the analysis of the problems of autistic children in inclusive schools SMK Negeri 9 Padang City and focused on autistic children in class XI Tataboga 3. Based on the results of research that had been carried out from interviews with key informants regarding "Analysis of the problems of autistic children in inclusive schools at SMK Negeri 9 Padang City "the researchers can conclude that the problems experienced by autistic children in inclusive schools are: The interaction of autistic children at school has started to improve from the beginning autistic children entered school until now they have become more open personalities and can interact comfortably with other students. Communication for autistic children at school is not really an obstacle because autistic children are mildly autistic and can still blend in and not be much different from other students. The behavior of autistic children at school is much better, they are rarely alone.